Trainee experience of 'out of hours' surgical working in the UK: A cross-sectional analysis. Issue 5 (October 2020) - Vaughan-Shaw, P.G.; Lineham, B.; Hurst, K.; McBride, O.; Honeyman, C.; Healy, S.; Banks, J.; Wickramasinghe, N.; Riding, D.M.; Moran, M.
Abstract: Background: Changes to working practices and increasing service demand have contributed to low morale amongst UK surgical trainees, with pressures particularly acute 'out of hours' (OOH). Surgeons may be expected to be 'on call' for multiple hospitals, or to provide remote consultations, yet healthcare systems may undermine their professional safety and patient care. This cross-sectional study sought to define the perceptions of UK-based Royal College of Surgeons of Edinburgh (RCSEd) affiliated trainees of OOH surgical care and training. Methods: The RCSEd Trainees' Committee conducted a design-thinking exercise to produce an online questionnaire. Non-consultant grade RCSEd Members and Fellows were invited to participate. Quantitative data was analysed using descriptive statistics, and qualitative data was coded to identify emergent themes. Results: One hundred and fifty-five surgeons participated. Of those surgeons working in multiple hospitals OOH ( n  = 16), many did not receive access cards (12[75%]) or site-specific induction (13[81%]), and 8(50%) were not confident in using local electronic investigation and records systems. Only 14/114 (12%) of the surgeons providing remote opinion had access to a consultation record system, and most perceived dissatisfaction with the system. Emergent themes from qualitative data revealed that trainee surgeons desire specific training in OOH working, concerns that OOH work experience is diminishing, and that hospital infrastructure such as IT and communications, rest facilities and catering were inadequate in facilitating safe care. Conclusions: The participants perceived that the systems supporting delivery of safe surgical care OOH were inadequate. Hospital leaders should ensure that systems minimise risk to staff and patients. Highlights: Systems that support 'out of hours' surgical care are perceived to be inadequate. Hospital infrastructure does not facilitate safe care. Surgeons covering multiple hospitals 'out of hours' do not feel adequately prepared. There is little training for surgeons providing remote consultation 'out of hours'.